Body mass index, exercise, and other lifestyle factors in relation to age at natural menopause: analyses from the breakthrough generations study. - Morris, D; Jones, M; Schoemaker, M; McFadden, E; Ashworth, A; Swerdlow, A (2012)
The authors examined the effect of women's lifestyles on the timing of natural menopause using data from a cross-sectional questionnaire used in the United Kingdom-based Breakthrough Generations Study in 2003-2011. The analyses included 50,678 women (21,511 who had experienced a natural menopause) who were 40-98 years of age at study entry and did not have a history of breast cancer. Cox competing risks proportional hazards models were fitted to examine the relation of age at natural menopause to lifestyle and anthropometric factors. Results were adjusted for age at reporting, smoking status at menopause, parity, and body mass index at age 40 years, as appropriate. All P values were 2-sided. High adult weight (P(trend) < 0.001), high body mass index (P(trend) < 0.001), weight gain between the ages of 20 and 40 years (P(trend) = 0.01), not smoking (P < 0.001), increased alcohol consumption (P(trend) < 0.001), regular strenuous exercise (P < 0.01), and not being a vegetarian (P < 0.001) were associated with older age at menopause. Neither height nor history of an eating disorder was associated with menopausal age. These findings show the importance of lifestyle factors in determining menopausal age.